Numerical investigation to explore the influence of combustion chamber modification on combustion and emission of a diesel engine fuelled with biodiesel. Issue 1 (31st December 2022) - Khan, Shahanwaz; Panua, Rajsekhar; Bose, Probir Kumar
Abstract : Computational fluid dynamics investigation has been conducted in a direct injection diesel engine to explore the performance of rapeseed methyl ester (RME) biodiesel blends with diesel operating with different combustion chamber geometries. The multidimensional commercial software code AVL FIRE is used for better understanding the parameters controlling the flow, combustion and emission processes. The modification in the combustion chamber profile may improve air–fuel mixing process to have better combustion. The simulation result shows that combustion chamber profile plays a crucial role in controlling the air and fuel mixture which has a direct impact on the performance and emission characteristics in compression ignition engines. The predicted results indicate that brake-specific fuel consumption is higher for biodiesel blends due to its lower heating value. However, a significant reduction in NOx and a relatively higher amount of soot have been observed for RME blends with diesel compared to base diesel.